(untitled) (Journal of Hama University, 2025)
This study was conducted on the (44) neighborhoods of the city of Hama - Syria. Noise levels were measured in all neighborhoods except for five of them: Al-Sabil neighborhood, which was almost completely demolished, Al-Zanbaqi and Al-Asidiya neighborhoods, Al-Nakrana neighborhood, which is under construction, and Al-Sinaa neighborhood. With the aim of determining its levels in the city, and dividing it into noise areas, using a noise measuring device (Digital Sound Level Meter 824 (Taiwanese origin), during a full academic year (2022), this study concluded that all areas in the city are polluted with noise, and there are multiple sources. The noise exceeded the standards set by the World Health Organization (WHO), and the Syrian standards set by the Syrian Arab Standards and Metrology Organization (SASMO).